2010
DOI: 10.1007/s11745-010-3412-5
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of Milk and Dairy Foods and the Incidence of Vascular Disease and Diabetes: An Overview of the Evidence

Abstract: The health effects of milk and dairy food consumption would best be determined in randomised controlled trials. No adequately powered trial has been reported and none is likely because of the numbers required. The best evidence comes, therefore, from prospective cohort studies with disease events and death as outcomes. Medline was searched for prospective studies of dairy food consumption and incident vascular disease and Type 2 diabetes, based on representative population samples. Reports in which evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
290
2
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 335 publications
(318 citation statements)
references
References 61 publications
11
290
2
9
Order By: Relevance
“…However, the potential health impacts of animal-derived foods, and more specifically Proceedings of the Nutrition Society milk and dairy consumption, have been questioned owing to their high saturated fat content (for review, see (3) ). However, emerging epidemiological evidence supports the beneficial effects of milk and dairy consumption on health, particularly cardiometabolic health (4)(5)(6) .…”
Section: Dairy Protein: Metabolic Health: Blood Pressure: Vascular Fumentioning
confidence: 99%
“…However, the potential health impacts of animal-derived foods, and more specifically Proceedings of the Nutrition Society milk and dairy consumption, have been questioned owing to their high saturated fat content (for review, see (3) ). However, emerging epidemiological evidence supports the beneficial effects of milk and dairy consumption on health, particularly cardiometabolic health (4)(5)(6) .…”
Section: Dairy Protein: Metabolic Health: Blood Pressure: Vascular Fumentioning
confidence: 99%
“…Elwood et al (2008) also examined four studies in which incident diabetes was the outcome, and RR in subjects with the highest intake of milk or dairy foods was 0.92 (95% CI 0.86, 0.97). This work has been extended to examine the evidence for the differential effects of milk, cheese and butter on the incidence of vascular disease (Elwood et al, 2010). This essentially found that there were very few prospective cohort studies available for cheese (five) and butter (six).…”
Section: Milk Dairy Products and Chronic Diseasementioning
confidence: 99%
“…However, by selecting individuals with highly elevated android body fat, we observed a significant effect of milk on attenuating postprandial hyperglycemia. These results are consistent with the previous observation that the beneficial effects of dairy on metabolic and clinical parameters are more likely to be evident in individuals with elevated risk factors for CVD as there appears to be a distinct “basement effect” associated with dairy intake, in which little to no changes have been observed in healthy individuals with normal or low values (Elwood et al., 2010; Pereira et al., 2002; Poppitt et al., 2002). Therefore, the observed effects can likely be extended to, and perhaps greater in, older obese adults, type 2 diabetes, and those with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant differences in glycemic responses between the trials involving nonfat milk and those with the control drink that included the same amount of protein. These results confirm previous findings that at least some of the beneficial effects of milk on glycemic responses can be attributed to its protein quantity (Akhavan et al., 2010, 2014; Ballard et al., 2013; Elwood et al., 2010; Fekete et al., 2016; Gannon et al., 1992; Jakubowicz et al., 2014; Manders et al., 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation